1863 Dakota Terr. Sess. Laws 47, 49, ch. 4, §§ 9-10 - (:unkn) unknown (General Publisher, 1863)
…Sec. 9. Every person who shall break and enter any dwelling house in the night time, with intent to commit the crime of murder, rape, robbery, larceny, or any other felony, or after having entered with such intent, shall break any such dwelling house in the night time, any person being then lawfully therein, and the offender being armed with a dangerous weapon at the time of such breaking, or entering, or so arming himself in such house, or making an actual assault on any person lawfully therein, shall be punished by imprisonment in the territorial prison not more than twelve years, nor less than four years. Sec. 10. Every person who shall break and enter any dwelling house in the night time, with such intent as is mentioned in the last preceding section, or who, having entered with such intent, shall break such dwelling house in the night time, the offender not being armed or arming himself in such house with a dangerous weapon, nor making an assault upon any person then being therein, shall be punished by imprisonment in the territorial prison not more than five years, nor less than two years.”
--
Keywords: COMMITTING CRIME W/ WEAPON